Notes on the norm of pre-Schwarzian derivatives of certain analytic functions - KARGAR, Rahim (Studia Universitatis Babeș-Bolyai Mathematica, 2020)
In this paper, we obtain sharp bounds for the norm of pre-Schwarzian derivatives of certain analytic functions. Initially this problem was handled by H. Rahmatan, Sh. Najafzadeh and A. Ebadian [Stud. Univ. Babe¸s-Bolyai Math. 61(2016), no. 2, 155-162]. We pointed out that their proofs are incorrect and present correct proofs. Mathematics Subject Classification (2010): 30C45.